Extraction of antioxidants with aqueous biphasic systems - Vaz, Tatiana Sofia Marçalo (2014)
Nowadays, antioxidants present a great relevance in a variety of applications used by the pharmaceutical and the cosmetic industries. The antioxidants are able to inhibit or to retard the oxidation of other compounds, and mainly the oxidation caused by free radicals, and that is the reason of their importance in the industry and their incorporation into a variety of products. For the utilization of antioxidants in effective quantities, it is necessary to either chemically synthesize them, what is expensive and may causes problems due to their non-natural origin, or to extract them from their natural sources (biomass). Conventional methods for the extraction of antioxidants and the following purification are normally expensive and time-consuming. Therefore, other extraction methods, like the liquid-liquid extraction using aqueous biphasic systems (ABS), have been studied. In this work, the use of ABS based on ionic liquids (ILs) and polymers is proposed as an alternative for the conventional systems that are mostly composed of polymers and inorganic salts. The use of ILs allows the tuning of the properties of the extraction systems by variation of their ions and so to increase the extraction efficiencies. In this work, it is shown, for the first time, that poly(vinyl pyrrolidone) (PVP) and poly(vinyl alcohol) (PVA) of different molecular weights form ABS with phosphonium-based and imidazolium-based ILs. The respective phase diagrams were determined at 25 °C to define the minimum concentrations that are necessary for the formation of two aqueous phases. Finally, the ability of these systems as liquid-liquid extraction systems was evaluated. To this end, the partition coefficients and extraction efficiencies of several antioxidants (gallic acid, vanillin, vanillic acid and syringic acid) using the studied systems were determined. Extraction efficiencies ranging from 75% to 95 % were obtained for the different systems, thus demonstrating their capability for extracting purposes. In general, the most efficient system for the extraction of antioxidants was that composed of the IL 1-butyl-3-methylimidazolium trifluoromethanesulfonate ([C4mim][CF3SO3]) and the PVA of 9,000-10,000 g.mol-1 (PVA9) for the extraction of all the studied antioxidants.